Laboratory Phonology 7
DOI: 10.1515/9783110197105.419
|View full text |Cite
|
Sign up to set email alerts
|

Gestural overlap and recoverability: Articulatory evidence from Georgian

Abstract: According to previous investigations of gestural patterning, consonant gestures exhibit less temporal overlap in a syllable/word onset than in a coda or across syllables.Additionally, front-to-back order of place of articulation in stop-stop sequences (labialcoronal, coronal-dorsal, labial-dorsal) exhibits more overlap than the opposite order. One possible account for these differences is that substantial overlap of obstruent gestures may threaten their perceptual recoverability, particularly word/utterance-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
0
1

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(99 citation statements)
references
References 20 publications
6
92
0
1
Order By: Relevance
“…This has been related to the importance of temporal structure in languages or to the lexical access to words, from left to right (cf. Nooteboom 1981, Hawkins & Cutler 1988, Barnes 2002, Chitoran et al 2002. From a phonetic point of view, Barnes (2002) has further proved that several effects attributed to the initial syllable are, in fact, strictly induced by the vowel appearing at the absolute left edge of the word, since this segment, among other things, is clearly longer than other vowels.…”
Section: Prominence: Word-initial Position and Sonoritymentioning
confidence: 98%
See 1 more Smart Citation
“…This has been related to the importance of temporal structure in languages or to the lexical access to words, from left to right (cf. Nooteboom 1981, Hawkins & Cutler 1988, Barnes 2002, Chitoran et al 2002. From a phonetic point of view, Barnes (2002) has further proved that several effects attributed to the initial syllable are, in fact, strictly induced by the vowel appearing at the absolute left edge of the word, since this segment, among other things, is clearly longer than other vowels.…”
Section: Prominence: Word-initial Position and Sonoritymentioning
confidence: 98%
“…From a phonetic point of view, Barnes (2002) has further proved that several effects attributed to the initial syllable are, in fact, strictly induced by the vowel appearing at the absolute left edge of the word, since this segment, among other things, is clearly longer than other vowels. Other scholars have argued that word-initial consonants may have a special status as well, which has to do with prominent effects stemming from the position in which they are located (see, among others, Chitoran et al 2002).…”
Section: Prominence: Word-initial Position and Sonoritymentioning
confidence: 99%
“…Since onset clusters can occur in utterance initial position, where there would be no acoustic cues from a preceding vowel as to the identity of C1, word-initial clusters may be timed with a wider lag in order to preserve the inherent information of C 1 (Chitoran et al, 2002). Consequently, we expected more overlap medially than initially.…”
Section: Physiological Studymentioning
confidence: 99%
“…Several psycholinguistic experiments have concluded that there is a noticeable left / non-left asymmetry, in that the left part of the word is more relevant than the end part of the word and even more relevant than the middle part of the word in word recognition. This has been related to the importance of temporal processing of words or to the lexical access to words, from left to right (see, among others, Nooteboom 1981, Hawkins & Cutler 1988, Barnes 2002, Chitoran et al 2002, Lloret & Jiménez 2008, and it explains, among other facts, why this position crosslinguistically favours finer faithfulness requirements (Beckman 1998;Casali 1996Casali , 1997, the accumulation of prominent properties (Crosswhite 1999(Crosswhite , 2004 or the preference for suffixing versus prefixing (Hawkins & Cutler 1988). In fact, the initial position of the word in the phonology of Catalan has been proposed to be relevant in previous work by Cabré & Prieto (2006) to explain the preservation of vocalic features and the blocking of glide formation in Catalan and Spanish, and in work by Lloret & Jiménez (2008) and Jiménez & Lloret (2010) to justify the occurrence of elements of high sonority in the phonology of Western Catalan dialects.…”
Section: F[é]sta → F[e]st[á]ssa V[e]rm[ú]t Esp[é]ra → Esp[e]r[á]u P[ementioning
confidence: 99%